Initial Assessment Knowledge Improves Primary Survey Implementation in Nurses in Emergency Rooms - Cirana, Viona Lioren; Muhaji, Muhaji; Azizah, Aisyah Nur (Journal Keperawatan, 2024)
Background: Emergency Room (IGD) is an installation room that provides health services in hospitals, especially for emergency patients who must immediately receive fast and appropriate treatment. Emergency nursing services must pay attention to the initial assessment which includes the primary survey and secondary survey. Initial assessment and follow-up are key to saving patient lives. Purpose: To find out the relationship between initial assessment knowledge and the implementation of a primary survey on nurses at the Emergency Room at PKU Muhammadiyah Gamping Hospital. Methods: Quantitative research method with correlational research design. The sampling technique used total sampling with a sample size of 29 respondents. The tools used in data collection were questionnaires and observation sheets. Data analysis used the Kendall's Tau statistical test. Results: Based on the results of the statistical test analysis, the p-value is 0.004 <0.05 with a number so that there is a relationship between the initial assessment and the implementation of the primary survey. The correlation coefficient value is 0.550, which means the relationship between the two variables is strong with a positive correlation number. Conclusion: There is a relationship between initial assessment and the implementation of primary surveys in nurses. The higher the nursing knowledge about initial assessment, the better the implementation of the primary survey.